2020
DOI: 10.1038/s41419-020-2684-9
|View full text |Cite
|
Sign up to set email alerts
|

TFAP2C facilitates somatic cell reprogramming by inhibiting c-Myc-dependent apoptosis and promoting mesenchymal-to-epithelial transition

Abstract: Transcription factors are known to mediate the conversion of somatic cells to induced pluripotent stem cells (iPSCs). Transcription factor TFAP2C plays important roles in the regulation of embryonic development and carcinogenesis; however, the roles of Tfap2c in regulating somatic cell reprogramming are not well understood. Here we demonstrate Tfap2c is induced during the generation of iPSCs from mouse fibroblasts and acts as a facilitator for iPSCs formation. Mechanistically, the c-Myc-dependent apoptosis, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 58 publications
0
26
0
Order By: Relevance
“…TFAP2C plays a vital role in initiating surface ectoderm differentiation, and TFAP2C-initiated progenitor cells can mature into functional keratinocytes ( Li et al, 2019 ). Moreover, TFAP2C can promote epithelial gene expression by directly binding to their promoters during induced pluripotent stem cell (iPSC) generation from mouse fibroblasts ( Wang et al, 2020a ). Further studies have shown that E-cadherin (CDH1), an important downstream target of TFAP2C and a critical regulator of EMT, plays a crucial role in mechanical stretch-induced skin cell regeneration and proliferation ( Huang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…TFAP2C plays a vital role in initiating surface ectoderm differentiation, and TFAP2C-initiated progenitor cells can mature into functional keratinocytes ( Li et al, 2019 ). Moreover, TFAP2C can promote epithelial gene expression by directly binding to their promoters during induced pluripotent stem cell (iPSC) generation from mouse fibroblasts ( Wang et al, 2020a ). Further studies have shown that E-cadherin (CDH1), an important downstream target of TFAP2C and a critical regulator of EMT, plays a crucial role in mechanical stretch-induced skin cell regeneration and proliferation ( Huang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…TF binding motif enrichment analysis of our data revealed that upon the treatment, there was an enrichment of several TF binding motifs, which play important roles in the process of reprogramming. Some TF binding motifs that were enriched in CEF after treatment, such as TEAD4 ( 63 ), TEAD3 ( 15 ), AP1 ( 15 , 64 ), NFAT: AP1 ( 65 ), AP2 ( 66 ), CEBP ( 67 , 68 ), MEIS2 ( 69 ), and NF-κB ( 70 , 71 ) are involved in the establishment of pluripotency. Specifically, the AP-1 family has previously been reported to impede somatic cell reprogramming ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings support the notion that the pioneer factor AP2 promotes the formation of a ZEB1-ER TF comple . Al ho gh AP2 main ain the mammary epithelial state in ER + breast cancers 68,69 , it can stimulate both EMT and MET by inducing open chromatin states [70][71][72] . Moreover, we discovered that ZEB1 significantly enhances the ER recr i men o the AP2 gene TFAP2C, re l ing in he preg la ion of AP2 .…”
Section: Discussionmentioning
confidence: 99%